Rsx is a metatherian RNA with Xist-like properties in X-chromosome inactivation - Grant, Jennifer; Mahadevaiah, Shantha K.; Khil, Pavel; Sangrithi, Mahesh N.; Royo, Hélène; Duckworth, Janine; McCarrey, John R.; VandeBerg, John L.; Renfree, Marilyn B.; Taylor, Willie; Elgar, Greg; Camerini-Otero, R. Daniel; et al. (Nature (London), 2012)
A non-coding RNA termed Rsx , which has properties consistent with a role in X-chromosome inactivation, is identified in the marsupial Monodelphis domestica . Marsupial X-chromosome inactivation In both eutherian (placental) and metatherian (marsupial) mammals, XX females undergo X-chromosome inactivation to ensure that they have the same dose of X-linked gene products as XY males. In eutherians, X-inactivation is initiated by the non-coding RNA Xist , but Xist is not conserved in metatherians, so the mechanism underlying X-inactivation in these mammals has been unclear. Here, a non-coding RNA termed Rsx that has properties consistent with a role in X-inactivation is identified in a marsupial —the grey, short-tailed opossum ( Monodelphis domestica ). Rsx is expressed only in females, is transcribed from and coats the inactive X chromosome, and is associated with gene silencing. Rsx and Xist lack significant sequence homology, which suggests that aspects of the X-chromosome inactivation pathway have evolved convergently. In female (XX) mammals, one of the two X chromosomes is inactivated to ensure an equal dose of X-linked genes with males (XY) 1 . X-chromosome inactivation in eutherian mammals is mediated by the non-coding RNA Xist 2 . Xist is not found in metatherians 3 (marsupials), and how X-chromosome inactivation is initiated in these mammals has been the subject of speculation for decades 4 . Using the marsupial Monodelphis domestica , here we identify Rsx (RNA-on-the-silent X), an RNA that has properties consistent with a role in X-chromosome inactivation. Rsx is a large, repeat-rich RNA that is expressed only in females and is transcribed from, and coats, the inactive X chromosome. In female germ cells, in which both X chromosomes are active, Rsx is silenced, linking Rsx expression to X-chromosome inactivation and reactivation. Integration of an Rsx transgene on an autosome in mouse embryonic stem cells leads to gene silencing in cis . Our findings permit comparative studies of X-chromosome inactivation in mammals and pose questions about the mechanisms by which X-chromosome inactivation is achieved in eutherians.